The gender gap in private pensions - Elena Bardasi; Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2004)
Older women in Britain receive considerably less private pension income than older men, on average. We analyse this differential by examining differences between the sexes both in private pension coverage and in pension income conditional on receipt. Using regression-based decompositions, we show that both gaps are associated mainly with gender differences in returns to personal characteristics rather than with gender differences in personal characteristics per se. In particular, although there are marked differences between elderly men and elderly women in their lifetime employment histories, these differences account for only a small fraction of the overall private pension income gap between the sexes.
Keywords: 330